PENGARUH METODE PICTORIAL RIDDLE TERHADAP HASIL BELAJAR SISWA DALAM PEMBELAJARAN MATEMATIKA PADA KELAS IX SMP NEGERI 1 KATEMAN - Sirajuddin '; Zuhri. D '; Sakur ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The research of the study was to determine the effect of the application of methods of pictorial riddle on learning outcomes in mathematics at grade IX SMP Negeri 1 Kateman . This research is a quasi experimental . The subjects were two classes that have been randomly after normality test and homogeneity test with the class as an experimental class and control class as a class . Experimental class is a class that is given treatment by applying the method . Data analysis technique used was t-test . Based on the final results of data processing obtained t > t table 1.924 > 1.66 meaning that the application of methods of pictorial riddle affect learning outcomes in mathematics class IX SMP Negeri 1 Kateman on the material similarity .Key words: Mathematics learning outcome, Pictorial Riddle Methode, Eksperiment research